The Effect of Credit Risk and Liquidity Risk on Bank Stability - Dwinanda, Ibnu Zakaria; Sulistyowati, Chorry (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2021)
The purpose of this study is to determine the effect of credit risk and liquidity risk on bank stability. This study used the multiple regression analysis to determine the effect of credit risk and liquidity risk as the independent variables, with BOPO (Biaya Operasional Pendapatan Operasional), GDP (Gross Domestic Bruto), BI Rate as the control variables, on Bank Stability as the dependent variable. Using purposive sampling method to collected data from the list of banking companies in OJK (Otoritas Jasa Keuangan) from 2013 to 2017 consisting of 437 observations. The estimated results show that credit risk has a significant negative effect on bank stability, and liquidity risk has a significant negative effect on bank stability. Whereas in the control variable, GDP does not affect bank stability, BOPO has a significant negative effect on bank stability, and the BI-Rate does not affect bank stability. Keywords: Credit Risk, Liquidity Risk, Bank Stability